Health Worker Survey in Timor-Leste - World Bank; Oxford Policy Management (World Bank, Dili and Oxford Policy Management, Oxford, 2016)
At the time of independence in 2002, Timor-Leste had a seriously weak health system with only a handful of doctors in the country. In this context, the governments of Timor-Leste signed an agreement and the Cuban Medical Brigade started to train medical students and deploy them in the country, particularly in rural areas. While the initial massive shortage has now been minimized, there are concerns over more complex issues including facility functionality, rural retention, motivation, preferences and competence of health workers. The objectives of this survey were to understand the labor market dynamics among health workers, to learn more about the preferences and concerns of health workers, and to assess the skills, competence and motivation of doctors.